Development and preliminary evaluation of a multi-component workplace wellness programme targeting overweight and obese workers / Nur Suffia Sulaiman - Nur Suffia, Sulaiman (2017)
Sedentary lifestyle and unhealthy diets contribute towards obesity and increase risks for the early development of non-communicable diseases in Malaysia. The workplace has been targeted for lifestyle intervention. In this quasi-experimental study, a 6-month „Healthy Worker Programme‟ was carried out at a worksite and compared to a control worksite. Both worksites were located in Federal Territories. The programme, a multicomponent intervention, based on the Socio-Ecological Model, promoted improvement in diets and physical activity (PA) of overweight and obese government office workers. The programme included workplace environment modification (eg. displays of health posters, top management support, healthier alternatives at the cafeteria), co-worker and individual motivation through monthly health information packs/newsletters. At mid-programme, a telephone call was made to respondents for feedback and advice. The primary outcomes were weight and body mass index. Secondary outcomes were physical activity, dietary intake and quality of working life. For assessment of quality of working life (QOWL), the Work-Related Quality of Life-2 Scale was translated into Malay and validated.Data collection was conducted at baseline, mid-programme (3rd month), programme end (6th month) and postprogrammme (9th month). Repeated measures analysis of covariates (ANCOVA) was carried out using modified intention to treat approach. A total of 283 workers enrolled into the study. At the intervention site, there were 51 males (39%) and 81 females (61%). At the control site, there were 69 males (46%) and 82 females (54%). Data from 183 office workers were analysed, that is 93 respondents from the intervention group and 90 controls. At programme end, the proportion who lost at least five percent of their original weight was 14% among the intervention group and 4% among controls (p=0.03). Those in the programme were 1.6 times more likely to lose this amount compared to controls (RR = 1.6; 95% CI: 1.2, 2.2). There was a significant mean iv difference of -0.6 kg/m2 in body mass index (BMI) change between the intervention and control groups (95% CI: -0.9, -0.3). The proportion who lost five percent of their original weight were 12% among the intervention group and 8% among controls at postprogramme. At programme end, respondents at intervention site were 1.3 times more likely to achieve 10,000 steps (95% CI: 0.8, 2.1). PA continued to improve and at postprogramme, they were 1.8 times more likely to reach 10,000 steps a day (95% CI: 1.2; 2.5). There was significant overall mean reduction of 3% carbohydrate daily intake between baseline and at programme end. An increase of mean QOWL score(especially through better „General Well-Being‟ and reduction of „Stress At Work‟ factors) was seen in the intervention group at programme end which continued modestly post-programme. The preliminary results show that the „Healthy Worker Programme‟ can reduce weight and BMI among overweight and obese workers, with sustainable changes in the short term. It may also improve workers‟ physical activity and QOWL. However, the programme would benefit from further improvement and evaluation before implementation widely.